Gamma‐aminobutyric acid (GABA) can affect physiological processes in preimplantation embryos via GABAA and GABAB receptors - Veronika Kovaříková; Alexandra Špirková; Zuzana Šefčíková; Jozef Pisko; Laura Kalatová; Juraj Koppel; Dušan Fabian; Štefan Čikoš (Reproductive Medicine and Biology, 2023)
Abstract Purpose Several widely used substances (e.g., some therapeutics or food supplements) can act on gamma‐aminobutyric acid (GABA) receptors, and we investigated whether the activation of these receptors could affect the preimplantation embryo. Methods Transcripts of all GABA receptor subunits and selected proteins were examined using quantitative RT‐PCR and immunohistochemistry. To analyze the effects of receptor activation, in vitro culture of mouse preimplantation embryos with natural and synthetic GABA receptor ligands was used. Results We detected nine GABA receptor transcripts in mouse blastocysts and 14 GABA receptor transcripts in ovulated oocytes. The results of this study indicate that ionotropic GABAA receptors can be formed from α5, β3, and γ3 (or δ, π) subunits, GABAA‐ρ receptors can be formed from ρ2 subunits and metabotropic GABA receptors can be formed from GABAB1b and GABAB2 subunits in mouse blastocysts. Supplementing the culture medium with GABA at concentrations of 2–10 mM or with specific GABAA and GABAB receptor agonists (at concentrations of 10–100 μM) significantly increased the proportion of dead cells in blastocysts. The GABA‐induced effects were prevented by pretreatment of embryos with GABAA and GABAB receptor antagonists. Conclusion The results of this study indicate that GABA and synthetic GABA receptor ligands can negatively affect preimplantation embryos via GABAA and GABAB receptors.